Pengenalan Algoritma Pemrograman Dasar Dalam Konteks Pembelajaran Pemrograman Awal - Armina Rangkuti; Yahfizham Yahfizham (International Forum of Researchers and Lecturers, 2023)
Algorithms are steps that are arranged logically and systematically to solve a problem. In the world of simple programming, the algorithm is the initial stage and is written before the program is written. One of the problems that can be solved with computer programming is problems that involve mathematical calculations. This research aims to develop understanding of algorithms and develop programming skills, especially for beginners. The method used in this research is the literature study or literature review method, namely analyzing several studies related to the topic discussed, especially introducing the basic concepts of programming algorithms, characteristics of programming algorithms, grouping programming languages ​​based on level and algorithm notation, which are some of the basic things that are mandatory. known by everyone who wants to create a program. This understanding will be very helpful in the development of more complex programming projects. Therefore, learning basic programming algorithms is very crucial or important for anyone who wants to start in the world of programming.